Diseño arquitectónico de un complejo deportivo para la parroquia de Cunchibamba del cantón Ambato, “Complejo Pucarrumi” - Chasi Condemaita, Carlos Daniel (2024)
Currently, the design of sports spaces plays an important role in people's lives, with physical activity and sport lies in its contribution to the population in the development of their personality to expand knowledge and discover skills. In the parish, the lack of interest and motivation in young people and children in sports and recreational activities has been identified, due to the lack of places where this type of events can be held. This affects the well-being and health of the population due to the lack of sports practices and the use of active and passive recreation. Through research, it lies in the implementation and improvement of spaces that promote physical activity, recreation and sports, in order to improve their quality of life and the development of the rural parish. The methodology has a mixed, qualitative and quantitative approach. The quantitative approach proposes an objective reality following a predictable and structured pattern, it also collects data that is based on measurement, is represented by quantities and analyzed with scientific methods. This approach makes it possible to identify statistical data through surveys and observation sheets, which support the research to propose the integrative project. In this way, contribute and solve the problem of inefficient spaces for sports and recreational activity, managing to encourage sports among the population. Based on this, the architectural design of a sports complex for the Cunchibamba Parish of the Ambato canton is intended, “Pucarrumi Complex” through sustainable strategies, lighting and materiality that is integrated into the place with green areas, sports areas to attract the population and tourists.